Influence of political changes on sport faculties in major Universities of Former Yugoslavia - Kürner, D. (Array, 2008)
Great political changes in the late 1980s led to the fall of Yugoslavia. Each republic consequentially became an independent state. Slovenia was the firs republic to separate from the socialist Yugoslavia, followed by Croatia. Slovenia was the only one to avoid serious military conflicts. Croatia, Bosnia and Herzegovina and Serbia suffered greatly during the years of war. The war marked the younger generations on all levels including education and sport. Since then each republic has had its own history. For example, Slovenia is now considered economically stable and is also a member of several important international organizations such as NATO and European Union. Croatia has already applied for EU membership, while Serbia is still marked by the war and has yet to finish the transition process. The research deals with the place of sport in Universities curriculum and how it is perceived by the students of Ljubljana, Zagreb and Belgrade University. The research comprises a questionnaire which was the same for all three Universities. The students were questioned about their value systems, motives and possibilities for sport activities, and also about the sport programmes they can choose, if any, and their quality.